Influence Product Quality, Sevice Quality, Perceived Price, Customer Satisfaction Towards Customer Loyalty: A Case Study of Supermarket Retail - Bashil Mukhlish; Binarin Tirto Andika (Cita konsultindo, 2025)
This study aims to analyze the influence of Product Quality, Service Quality, Perceived Price, and Customer Satisfaction on Customer Loyalty in the supermarket retail industry in Indonesia. This study is based on the Stimulus-Organism-Response (S-O-R) theory, which explains how external stimuli such as product quality, service, and price can influence consumers' internal responses in the form of satisfaction, which ultimately affects loyalty. The research method used is a quantitative approach with a causal research type. Primary data was obtained by distributing questionnaires to 276 respondents who are supermarket consumers in various regions of Indonesia. Data analysis was performed using multiple linear regression with SPSS software. The results showed that Product Quality, Service Quality, and Perceived Price had a positive and significant effect on Customer Loyalty, while Customer Satisfaction did not have a significant effect on Customer Loyalty. These findings indicate that consumer loyalty is more influenced by product quality, service, and price than by satisfaction alone. The managerial implications of this study emphasize the importance of supermarket management to improve product and service quality, set competitive pricing policies, and build long-term relationships with customers through loyalty programs.